Implementation of Authentic Assessment in History Learning at SMA Negeri 1 Semarang - Nurhayati, Ela; Jayusman, Jayusman; Ahmad, Tsabit Azinar (Universitas Negeri Semarang, 2021)
The purpose research is to know the teacher's understanding of authentic assessment on the curriculum of 2013 in SMA Negeri 1 Semarang, to see the implementation of authentic assessment conducted by teachers in SMA Negeri 1 Semarang, and to know the obstacles experienced by teachers in SMA Negeri 1 Semarang in authentic assessment. The research method used is a qualitative case study. The research location is in SMA Negeri 1 Semarang. This study's data sources are information from the deputy head of school curriculum, teachers and learners, learning activities, documents, and questionnaires. Data collection techniques include the interview method, documentation study, and observation. The results of this study show that history teachers have a good understanding of authentic assessment in the 2013 curriculum; history teachers have performed a good assessment of knowledge and skills assessment, while in terms of analysis and reporting of authentic assessment results, teachers use online value processing software; obstacles experienced by history teachers is the plurality of learners with different backgrounds and characters, while the factors that support teachers in implementing authentic assessment are quality learners, the availability of facilities and learning resources and the existence of software processing value.